Modern Approach to SAH in Intensive Care Unit (ICU) - Bruder, N. (Centauro S.r.l., 2008)
SAH is still a severe pathology carrying a high risk of death or severe neurological morbidity. New diagnostic, monitoring and therapeutic methods are available for the detection and treatment of vasospasm. This includes transcranial Doppler, CT or MRI perfusion scan, protein S100B dosage, cerebral blood flow monitoring at the bedside. Medical treatment of vasospasm relies on increased blood pressure and dobutamine. Emergency balloon angioplasty or arterial vasodilator infusion is mandatory in case of vasospam-induced ischemic deficit. Despite several medical advances in the treatment of subarachnoid haemorrhage (SAH) due to aneurysm rupture, particularly interventional neuroradiology, it remains a potentially devastating illness with a high mortality rate. The most important determinant of outcome is neurologic state on arrival in the hospital, assessed with the World Federation of Neurological Surgeons (WFNS) scale (table 1)(1). Delayed cerebral ischemia due to cerebral vasospasm and medical complications due to SAH have both a major impact on outcome. The cooperative aneurysm study, including 457 patients with SAH, showed that the proportion of deaths from medical complications (23%) was comparable with the proportion of deaths attributed to the direct effects of the initial hemorrhage (19%), rebleeding (22%), and vasospasm (23%) after aneurysmal rupture (2). Thus, the aim of ICU management is to prevent or to limit the consequences of vasospasm and to treat medical complications that can have an adverse effect on the brain.